Design considerations for high-capacity and wide-area messaging using bluetooth technology - De Guzman, Mar Francis D.; Marciano, Joel Joseph S. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Bluetooth wireless technology has been widely adopted in most of the modern devices and is still being developed to deliver more powerful communication solutions. Due to increasing involvement of these Bluetooth-enabled devices in our daily activities, its capabilities are also becoming pervasive. However, its benefits are not being fully utilized due to the coverage and scalability limitations for the technology. In order to address these issues, a sector-based transmission with multi-radio Bluetooth system is proposed. The study primarily focuses in the design of a transceiver array front-end that combines these two methods together. Due to the co-location of multiple Bluetooth networks, also known as piconets, one critical consideration in the design is the reduction of inter-piconet interference (IPI). This requires the incorporation of a power-detector controlled RF switch and a leakage canceller in the design. It was found that the configuration developed has minimal sensitivity to load variations. The combined isolation performance achieved is around -53.61dB which is sufficient to avoid at the minimum the adjacent (2 MHz) interference. Furthermore, the network performance of the system under the effect of IPI was also derived. For a 3-sector and 4-radio Bluetooth system, the packet collision probability (PCP) is found to be 0.121 while the system throughout is found to be around 10 times higher. The results of the study could enable applications the require immediate, high-capacity, and wide-area wireless network based on Bluetooth technology.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Bluetooth technology; Wireless communication systems